ANALISIS PEMILIHAN RUTE PELAYARAN GUNA EFISIENSI WAKTU DAN KESELAMATAN DALAM BERLAYAR DI KAPAL MV. SPOB SEROJA III - Aldi Herdinansyah Sinaga; Rosnani; Bayu Yudho Baskoro; Fauziah Roselia; Rizal Rochmansyah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study analyzes the selection of shipping routes on MV Spob Seroja III to improve time efficiency and sailing safety amid increasing competition in the shipping industry. The research applies a triangulation method by collecting data from various sources, methods, and timeframes. The results show that route selection is carried out through three main stages: route identification, navigation planning, and safety planning. Careful and up-to-date planning based on publications and weather conditions is essential to ensure safe and efficient voyages.